PEMBERDAYAAN KEWIRAUSAHAAN DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BAGI KOMUNITAS USAHA MINUMAN CENDOL DI DESA PEGUYANGAN DENPASAR - Senimantara, I Nyoman; Riasning, Ni Putu; Amlayasa, Anak Agung Bagus (UNHI Press, 2025)
The existence of partners located in Peguyangan Village, North Denpasar District, are generally managed independently. The common problem faced by partners today is in developing their business to become bigger. Partner business productivity has not fully met the market criteria, because in measuring the productivity of partner businesses it is not supported by knowledge resources and good financial governance. Business loans proposed by partners to the Bank as the largest funding institution, have not been able to fulfill the stages or absolute requirements put forward by the bank regarding the preparation of accountable and transparent financial reports. In connection with partner problems, the orientation of the program is to provide education and training to partners as micro/service business actors, so that they are able to prepare their financial reports independently and responsibly. So that the capital capabilities of micro business partners/services are feasible to develop their business. The solution offered by the executor of community service is training in preparing financial reports using simple bookkeeping techniques. The application of science and technology referred to in this activity is to assist business actors in managing their business finances easily. With the intent and purpose of providing training on preparing reports for these partners, it can assist business actors in managing their financial traffic in a professional manner. The results of this community service activity are partners who have knowledge and understanding of financial management and are able to prepare financial reports for their business.